2021
DOI: 10.1371/journal.pone.0257010
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) enhances internal source monitoring abilities in healthy participants

Abstract: Source monitoring refers to the ability to identify the origin of a memory, for example, whether you remember saying something or thinking about it, and confusions of these sources have been associated with the experience of auditory verbal hallucinations (AVHs). Both AVHs and source confusions are reported to originate from dysfunctional brain activations in the prefrontal cortex (PFC) and the superior temporal gyrus (STG); specifically, it is assumed that a hypoactive PFC and a hyperactive STG gives rise to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is worth noting that their study did not incorporate distractor words, a key element present in our research. The absence of such a challenge in their task might have masked potential differences that were present in our study 25 . Other studies have observed no significant effects in healthy individuals when stimulating the STG with anodal tDCS 20 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is worth noting that their study did not incorporate distractor words, a key element present in our research. The absence of such a challenge in their task might have masked potential differences that were present in our study 25 . Other studies have observed no significant effects in healthy individuals when stimulating the STG with anodal tDCS 20 .…”
Section: Discussionmentioning
confidence: 87%
“…While formulating our study design, we encountered a study akin to ours, where tDCS was found to enhance internal source monitoring abilities in healthy participants with same montages 25 . This study shared similarities with ours, but a pivotal distinction was observed.…”
Section: Introductionmentioning
confidence: 99%